THE EFFECTIVENESS OF CAREER GUIDANCE INFORMATION SERVICES TO IMPROVE CAREER PLANNING OF EARLY SEMESTER STUDENTS - Hasana, Uswatun; Rasmanah, Manah; Putra, Bela Janare (LP2M IAI Al-Khairat Pamekasan, 2025)
This study discusses the Effectiveness of Career Guidance Information Services to Improve Career Planning for Early Semester Students. Aims to determine student career planning before and after being given career guidance services, and whether career guidance services are effective in improving student career planning. The research method is a quantitative approach, with the type of experimental research, the research design uses quasi-experimental one-group pretest-posttest, data collection techniques using questionnaires, and documentation. From a population of 82 people, researchers only drew a sample of 24 people who had met the criteria in the sampling. Data analysis techniques using normality tests, and t-tests. The results showed that the description of career planning in students before being given career guidance services was in the moderate category with an average pretest score of 55.63. In the description of career planning in students before and after being given career guidance information services, there were 21 students in the moderate category. Based on the test results of the effectiveness of career guidance information services to improve career planning for early semester students, Asymp. Sig (2-tailed) is 0.001. The value of 0.001 <0.05, it can be concluded that Ha is accepted and H0 is rejected, meaning that there is a difference between the pretest and posttest results. So it can be concluded that career guidance services are effective for improving the career planning of early semester students.